Determinants of Company Value: Pre and Post Crisis Global 2015 - Witasari, Okti; Cahyaningdyah, Dwi (Universitas Negeri Semarang, 2021)
The purpose of this research was to study the determinant of the value of companies pre-and post-crisis global 2015 about companies registered on the Indonesian Stock Exchange 2012 - 2018. The population of this research were companies registered on the Indonesian Stock Exchange 2012 - 2018. The number of samples were 906 datas consist of 151 companies. The research sample was taken using purposive sampling technique. The datas analysis in this research used descriptive statistical analysis, a test model with the best panel data regression estimation, and multiple analysis. The model test results showed that the best panel data estimation model was the fixed effect model, while the best post data crisis estimation model was the random effect model. The hypothesis test results showed that institutional ownership did not influence with pre- and post-crisis company values, capital structure has a significant positive effect on pre- and post-crisis company values, company size had a significant negative effect on pre-crisis company values, and company size did not influence post-company value crisis. The conclusions of this research were that no contradiction about institutional ownership and capital structure to the values of the company both pre and post crisis, while the size of the company was related to the values of the company, where the pre-crisis influenced significant negative effect and post-crisis did not influence.